PENGARUH WARNA OVITRAP TERHADAP JUMLAH TELUR NYAMUK Aedes aegypti - Linda Putri Darwamati; Tri Wahyuni Sukesi (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2021)
Aedes aegypti mosquito is a vector of the dengue virus which causes dengue hemorrhagic fever (DHF). Efforts that can be made to overcome the spread of dengue fever by controlling vectors, one of which is by breaking the vector life cycle using an egg trap (ovitrap). This study aims to determine the ability of Aedes aegypti mosquitoes to lay eggs on ovitrap color differences, determine the ovitrap color with the highest number of Aedes aegypti mosquito eggs, determine the difference in ovitrap color to the number of trapped Aedes aegypti mosquito eggs and determine the average difference between various ovitrap colors in Ahmad Dahlan University Rearing Laboratory from July to August 2020. This research method is One Group Design. Three repetitions were carried out with a plastic bottle that was painted black, transparent, green, blue, purple and yellow. The 90 blood-saturated mosquitoes were put into three cages containing various colors of the ovitrap which had been given water and filter paper to place the eggs. The results showed that the Aedes aegypti mosquito would lay eggs on each ovitrap color and the number of mosquito eggs was mostly found on black ovitrap as many as 2978 eggs. Anova analysis showed that there was a significant difference in each ovitrap color to the number of trapped mosquito eggs and Benferroni's Post Hoc analysis showed that there was a significant difference between black means ovitrap with purple ovitrap and black and yellow color ovitrap